A signal-enhanced lateral flow strip biosensor for ultrasensitive and on-site detection of bisphenol A. Issue 1 (1st January 2018) - Peng, Xiayu; Kang, Lichao; Pang, Fangqin; Li, Hongmin; Luo, Ruifeng; Luo, Xiaoling; Sun, Fengxia
ABSTRACT: A signal-enhanced lateral flow strip biosensor has been constructed for ultrasensitive and on-site visual detection of bisphenol A (BPA). The signal amplification principle is based on the capacity of binding a large number of antibody-assembled gold nanoparticle (AuNP–antibody) conjugates of the poly amidoamine (PAMAM), which bears a multitude of amino groups. This signal-enhanced method could achieve BPA detection at 10 ppb based on naked eye visual observation, which represents an at least 50-fold improvement of the sensitivity of a traditional method without PAMAM. Moreover, good linearity was observed in the range from 2 to 100 ppb after quantitative analysis using the ImageJ software. This signal amplification method could be adopted as a potential generous technique in different fields.